AKUNTABILITAS PENGELOLAAN BADAN USAHA MILIK DESA (Studi Fenomenologi pada BUMDesa Gerbang Lentera di Desa Lerep, Kecamatan Ungaran Barat, Kabupaten Semarang, Jawa Tengah) - Ade Gustia Nugroho; Warsito Kawedar (Diponegoro Journal of Accounting, 2021)
This research focuses on the application of the principle and practice in the accountability of village enterprise management (BUM Desa). This research is expected to be beneficial to the Semarang District Government, especially Lerep Village Ungaran Barat Subdistrict in an effort to increase management accountability of village enterprise management for future directions. The method used in this research is qualitative approach. Sources of data was primary, the primary data were collecter through in-depth interview with key informant in each element of village government and staffs of BUM Desa Gerbang Lentera Lerep Village, that are considered to represent the research informant in the accountability of the Village Enterprise Management.This results of this research indicate that the planning process is in accordance with the regulations in the statutory of regulations, then monitoring and community empowerment has reflected part of the implementation of the accountability process, while the management and accountability of BUM Desa Gerbang Lentera is considered accountable and transparent both technically and administratively. The suggestion from this research is the need for more guidance to the village government officials and human resource competencies, so that they can run a more structured and in accordance with the regulations on an ongoing basis.